STUDENT PERCEPTION OF THE NEW PARADIGM INDEPENDENT CURRICULUM AT PIAUD - Windasari, Indriana Warih (E-CHIEF Journal, 2024)
This research aims to determine the perceptions of PIAUD undergraduate students regarding the new paradigm of an independent curriculum at the Early Childhood Education level. Data collection used an open questionnaire using purposive sampling techniques. The Method uses a descriptive qualitative with a case study. The location used is in the Early Childhood Islamic Education Study Program (PIAUD) Muhammadiyah Probolinggo Islamic College. The research subjects were all students of the 4th semester Islamic Early Childhood Education study program, totaling 19 people who took the Early Childhood Learning Design course. The result shows that the content and structure of the independent curriculum are substantively more simple and deeper, because it is focuses on the self-development of students, students have diverse opinions regarding the independent curriculum where in learning the Independent curriculum students are trained to express opinions with more critical, creative, and motivated in solving every learning challenge they face,  and teachers are required to be more creative in determining and designing learning activities by adjusting the conditions and needs of each class.